ENHANCING THE STUDENTS’ IN MASTERING WRITING ABILITY THROUGH CASE BASED METHOD - Dianing, Ernanda; Misnar, Misnar (Journal of English Education and Social Science, 2023)
The title of this research is Enhacing the Students’ in Mastering Writing Ability Through Case Based Method ( A Collaborative Classroom Action Research to the second year students of SMAN 2 Bireuen). The researcher found some problems of the research : First, How does Case Based Method enhance the students’ writing ability at the second year students of SMAN 2 Bireuen?. The second, How do the students’ response when teacher implemented Case Based Method used in teaching writing to the second year of SMAN 2 Bireuen?. The purposes of the research: First, To find out the use of Case Based Method enhanced the students of SMAN 2 Bireuen in writing ability. Second, To find out the students’ response toward the teacher implementing Case Based Method in teaching writing to the second year students of SMAN 2 Bireuen. The methodology used in this research is a collaborative Classroom Action Research. The instruments used in this research were: test, observation, questionnaire and field notes. Both qualitative and quantitative were combined in this research. Instruments used for qualitative research methodology were observation sheet for the teacher, observation sheet for the students, questionnaire and filed notes. Instruments used for quantitave was test. The result of this research show that Case Based Method was sucsess in enhancing the students’ writing ability, it is proved by mean score of the students test in the first cycle was 65.25% while the mean score of the students in cycle 2 was 78.6%. Futhermore, the mean score of the students response toward the implementation of Case Based Method was categorized strongly agree, it proved that the students had positive response toward the implementation of Case Based Method. The mean score of the teacher’s performance in the first cycle was 62,5% , while in the second cycle was 86,87%. The students were actively involved in teaching and learning process in the first cycle was 67,5% and in the second cycle was 86,25%. In conclusion, Case Based Method has successfull improved the students’ writing ability and the students had positive response toward the implementation of the Method.